Comparative study of curative effect of spinal endoscopic surgery and anterior cervical decompression for cervical spondylotic myelopathy - Yuan, Heng (J Spine Surg, 2020)
BACKGROUND: The aim of this study was to compare the clinical efficacy of endoscopic cervical spinal surgery with anterior cervical decompression and fusion (ACDF) in the treatment of cervical spondylotic myelopathy (CSM). METHODS: A total of forty-six CSM patients who were admitted to the Medical School of Chinese PLA and treated with endoscopic spine surgery or ACDF from January 2015 to June 2017 were collected. The patients were divided into the spinal endoscopy group and the ACDF group, according to the operation methods. The operation time, intraoperative blood loss and hospitalization stay of the two groups were recorded and compared. Japanese Orthopaedic Association (JOA) score before operation, three months, and one year after operation were recorded for intra-group and inter-group comparison. The improvement rates of JOA were compared between the two groups to evaluate the clinical efficacy. RESULTS: There were twenty-two cases in the spinal endoscopy group and twenty-four cases in the ACDF group. The mean operation lasting time, intraoperative blood loss and hospitalization stay in the spinal endoscopy group were significantly lower than those in the ACDF group (P<0.05). The postoperative JOA score of the two groups were significantly higher than those before the operation (P<0.05). There were no significant differences in the JOA score before operation, three months and one year after operation between the two groups (P>0.05). The improvement rates in the spinal endoscopy group were not significantly different compared to those in the ACDF group (P>0.05). There was no significant difference in the excellent rate (81.8% vs. 83.3%) between the spinal endoscopy group and the ACDF group (P>0.05). CONCLUSIONS: The short-term efficacy of spinal endoscopic surgery and ACDF was equal in the treatment of CSM. The spinal endoscopic surgery was significantly superior to ACDF in reducing the operation time, the intraoperative blood loss and the hospitalization stay.